Performance analysis on thermal energy storage unit for an atmospheric water harvester in museum display case. (15th August 2022) - Huang, Y.; Shi, W.K.; Liu, W.; Zhang, X.J.; Jiang, L.; Liu, D.P.; Zheng, Y.M.
Abstract: To control the humidity of museum display cases to protect historic relics, a small atmospheric water harvester is proposed for water replenishment which is integrated with a shell-and-tube latent thermal energy storage (LTES) to store off-peak electricity. Numerical models of water harvester with shell-and-tube LTES are established, and an experiment is conducted for model validation. It is indicated that higher inlet air temperature of water harvester brings more collected water, and inlet air temperature of 220 °C can meet the water demand. Heating power and geometrical parameters of shell-and-tube LTES are designed with two adjustable excess factors. The excess factors are found positively related to the outlet air temperature and melting rate in the charging and discharging process. To ensure complete melting of phase change material (PCM), a power excess factor of 1.6 is necessary. The system is tested in a day, and it is demonstrated that water demand of display cases can be met with the designed system. When PCM excess factor is 1.1 and power excess factor is 0.8, maximum annual total cost saving of $1.88 is achieved. The results provide reference for the design of heat storage equipment for atmospheric water harvester. Highlights: A latent thermal energy storage is combined with a small atmospheric water harvester. Output air temperature should be higher than 220 °C to meet water demand. Higher PCM amount and heating power can enhance daily collected water. Optimal annual total cost saving is $ 1.88 with the introduction of energy storage.